Associations between Autoimmunity and Depression: Serum IL-6 and IL-17 Have Directly Impact on the HAMD Scores in Patients with First-Episode Depressive Disorder - Lijuan Mao; Xiajin Ren; Xin Wang; Feng Tian (Journal of Immunology Research)
Objective. The study is aimed at evaluating the immune-activation state before and after treatment in patients with first-episode depressive disorder (FDD) with evaluating the ILs and CRP levels and further clarifying the association between autoimmunity and the etiology and pathogenesis of FDD. Methods. We designed a case-control study. FDD patients and healthy subjects were enrolled in the FDD group and control group. Serum IL-6, IL-17, and CRP were measured before and after selective serotonin reuptake inhibitor (SSRI) therapy, as well as Hamilton rating scale for depression (HAMD) and life event scale (LES) scores. The correlations between IL-6 and IL-17 and HAMD and LES scores were analysed, and multiple linear regression analysis was performed for HAMD score. Results. 40 FDD patients and 40 healthy subjects were included in the FDD and control group from October 2009 to September 2012. Before treatment, the IL-6 (28.99±5.51, P<0.001) and IL-17 (41.15±4.80, P<0.001) in the FDD group were significantly higher than the control group (16.84±3.78 and 21.68±3.72, respectively). The C-reactive protein (CRP) level in two groups was comparable (P=0.879). After treatment, the IL-6 (18.69±5.07, P<0.001) and IL-17 (30.67±3.47, P<0.001) levels and HAMD scores (6.73±4.15) in the FDD group were significantly decreased than before treatment (P<0.001, respectively). CRP level was slightly increased after treatment without statistically significant (P=0.239). The HAMD score correlated with IL-6 (r=0.638, P<0.001) and IL-17 (r=0.927, P<0.001); the total LES and negative LES also correlated with IL-6 (r=0.226, P<0.05) (r=0.366, P <0.001) and IL-17 (r=0.348, P<0.001) (r=0.493, P<0.001). Multiple linear regression analysis showed that both of the IL-6 and IL-17 had direct impact on HAMD score. Conclusion. The autoimmunity status was overactivated in FDD patients, and serum IL-6 and IL-17 levels had direct impact on the HAMD score. Patients who experienced more negative life events had higher activation level of autoimmunity status and HAMD scores, and serum IL-6 and IL-17 levels can be decreased by SSRI treatment.